1983
DOI: 10.1002/hlca.19830660709
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Participation in the Solvolysis of 6‐ and 7‐Substituted 2‐Norbornyl p‐Toluenesulfonates. Norbornanes, Part 11

Abstract: SummaryThe solvolysis rates and products of several 7-anti-substituted 2-endo-norbornyl p-toluenesulfonates 11 have been determined and compared with those of the previously reported 6-exo-substituted 2-exo-norbornyl p-toluenesulfonates 1. Although the number of bonds between the substituent and the reaction site is the same in the two series, the inductive effect of the substituents is transmitted far more strongly in the 6-exo-2-exo-series 1 than in the 7-anti-2-endo-series 11; i.e. their inductivities diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1983
1983
1988
1988

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…2 ) . This finding confirms that bridging of C (6) or C (7) is insignificant in the transition state for the 2-endo-series 2 [l] [3], so that the more localized charge at C(2) tends to increase the importance of solvent ionizing power. Apparently, solvent nucleophility does not play an appreciable role.…”
Section: ')supporting
confidence: 70%
See 2 more Smart Citations
“…2 ) . This finding confirms that bridging of C (6) or C (7) is insignificant in the transition state for the 2-endo-series 2 [l] [3], so that the more localized charge at C(2) tends to increase the importance of solvent ionizing power. Apparently, solvent nucleophility does not play an appreciable role.…”
Section: ')supporting
confidence: 70%
“…These results confirm that, due to differential bridging strain, 2-norbornyl cations are anisotropic to polar effects.Introduction. -Recent studies [l] [2] [3] have shown that the solvolysis rates of the 6and 7-substituted 2-exo-and 2-endo-norbornyl p-toluenesulfonates (tosylates) 1, 2, 3 and 4 in 80% EtOH are strongly dependent on the position and orientation of the substituents relative to the nucleofugal tosyloxy group. In fact, the response of rates to the I-effect of the substituents, the so-called inductivity of the system'), varied from -2.0 for the series 1 to -0.72 for the series 4, although the number of bonds between the substituent and the reaction site is the same in all cases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since bridging of C(2) by C (7) is at a minimum in the latter series [3] it should be negligible in the case of the series 2.…”
Section: 5mentioning
confidence: 99%
“…Meanwhile, it has been shown that the rates of the secondary 6-substituted 2-exo-norbornylp-toluenesulfonates (tosylates) 3 (X = OTsj are far more sensitive to the inductive ( I ) effect of the substituents than the rates of the 2-endo-epimers 4 [2] and of the 7-anti-substituted 2-endo-tosylates 5 [3]. This finding implied that inductivity [4] is especially high in the secondary 2-exo-6-exo-series 3 and led to the conclusion that through-space induction involves graded participation, or bridging, of C (6) in the ionization step.…”
mentioning
confidence: 99%